Comparative Study of Interlocking Nailing versus Dynamic Compression Plating in Fractures of Tibia in a Secondary Level Hospital in Bangladesh - Rahman, Md Asjadur; Mohammed, Khandaker Haris; Sinha, Sanjoy (Journal of Shaheed Suhrawardy Medical College, 2023)
Introduction: Tibial diaphyseal fractures are the commonest long bone fractures in adults, most commonly managed by intramedullary interlocking nailing. However, several metaanalysis show that locking plate osteosynthesis is equally effective in managing tibial diaphyseal fractures and are associated with less number of complications. Aim: To compare the results of fixation of tibial fractures following plating and nailing in terms of union, patient satisfaction and complications. Materials and Methods: A hospital based non randomized clinical trial was performed from January 2018 to December 2019 where closed or open diaphyseal or metaphyseo-diaphyseal fractures of the tibia (closed or open Gustilo Anderson type 1 through 3B) were included. Simple sequential allocation was used for allotting the patients to two groups, one for interlocking nailing and other for plating. The patients were followed up for clinical, radiographic and functional results. Results: Thirty patients with 30 involved limbs completed follow up for one year. The duration of surgery and average blood loss during surgery was 75.45±3.03 minutes and 165.00±5.31 ml respectively in case of nailing and 85.05±2.54 minutes and184.29±5.33 ml respectively in case of plating and their difference was statistically significant. In our study union was achieved in less than 20 weeks in 21 (70%) of the patients and 25-30 weeks in nine (30%) cases. The average time of union in our study was 19.55±0.69 weeks in case of interlocking nailing and 20.38±1.39 weeks in case of plating and there was no statistically significant difference between the two. However, there is statistically significant difference in the functional score in between the two groups in terms of Lower Extremity Functional Score (LEFS). Delayed union in one case of nailing and two cases of plating, valgus malunion in one case of nailing and joint stiffness in two cases each of nailing and plating were the major complications observed. Conclusion: There was no difference between the two modalities in terms of fracture union. Complications were lesser but more serious in case of plating. Patient satisfaction was more with plating. J Shaheed Suhrawardy Med Coll 2021; 13(2): 100-104